2022
DOI: 10.3390/wevj13080152
|View full text |Cite
|
Sign up to set email alerts
|

Peak Shaving for Electric Vehicle Charging Infrastructure—A Case Study in a Parking Garage in Uppsala, Sweden

Abstract: The need for a more flexible usage of power is increasing due to the electrification of new sectors in society combined with larger amounts of integrated intermittent electricity production in the power system. Among other cities, Uppsala in Sweden is undergoing an accelerated transition of its vehicle fleet from fossil combustion engines to electrical vehicles. To meet the requirements of the transforming mobility infrastructure, Uppsala municipality has, in collaboration with Uppsala University, built a full… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…If the load has a high load factor originally, it could be reduced by implementing controlled charging and V2G. This is illustrated and analyzed in [27,28]. Secondly, EVs could also be used strategically in smaller energy systems consisting of one or a few loads together with local generation from, e.g., solar PV, potentially operating in island mode using the car batteries to balance the system.…”
Section: Resilience Of the Grid And Ancillary Servicesmentioning
confidence: 99%
“…If the load has a high load factor originally, it could be reduced by implementing controlled charging and V2G. This is illustrated and analyzed in [27,28]. Secondly, EVs could also be used strategically in smaller energy systems consisting of one or a few loads together with local generation from, e.g., solar PV, potentially operating in island mode using the car batteries to balance the system.…”
Section: Resilience Of the Grid And Ancillary Servicesmentioning
confidence: 99%
“…For example, in [9], a possible design of charging infrastructure for company locations is presented while considering charging preferences and trip data of a bakery in Germany. A threeday experiment in a so-called "mobility house" (containing student housing, a grocery store, and a parking garage) showed that rule-based peak shaving and load demand forecasting can reduce load demand peaks by 25.4-38.5% while ensuring a minimum SoC of 50% [10]. The applicability of smart charging approaches that were designed specifically for charge-at-work scenarios, such as [11,12], and various related scheduling strategies, e.g., refs.…”
Section: Introductionmentioning
confidence: 99%